Fracture toughness and wear resistance of heat-treated H13 tool steel processed by laser powder bed fusion - Fonseca, Eduardo B.; Gabriel, André H.G.; Ávila, Julián A. [UNESP]; Vaz, Rodolpho F.; Valim, Diego B.; Cano, Irene G.; Lopes, Éder S.N. (Elsevier, 2023)
In today's industry, complex parts made of steel are a reality thanks to the introduction of additive manufacturing, which offers technological improvements in conventional and large manufacturing industries that rely on molds and dies for mass production. However, the rapid solidification, remelting and reheating during the process and the uneven properties of the parts might present some difficulties in expanding its application in some sectors. For example, H13 tool steel offers exceptional properties, but finding the correct post-heating treatment for additively manufactured parts with reliable and repeatable properties is still a challenge. In this study, we focused on investigating different heat treatments to better understand the microstructure evolution and consequently the mechanical behavior under quasi-static loads, fracture toughness and wear resistance. Conclusions could be drawn on the structure-property relationships involving the strengthening and toughening mechanisms, as well as the evolution of the martensitic microstructure, retained austenite and carbides in parts processed by laser-based powder bed fusion. We found that low temperature tempering (550 °C) provides the lowest fracture toughness (KQ = 36 MPa.m0.5, J = 6.5 kJ.m−2, δ = 2.0 µm), the highest mechanical strength (YS up to 2270 MPa) and the lowest wear rate (circa 2.0 ×10−5 mm3/N.m). On the other hand, high temperature tempering (650 °C) with prior austenitizing and quenching provides the best fracture toughness (KQ = 87 MPa.m0.5, J = 70 kJ.m−2, δ = 40 µm), average mechanical properties (YS = 1104 MPa) and wear rate (3.4 ×10−5 mm3/N.m). Thus, different heat treatment processes can be applied depending on the requirements of the project.
Keywords: Compression; CTOD; Hardness; J-Integral; KIC; Mechanical properties; Microstructure; Powder bed fusion; Tempering; Tool steel